The feasibility of discriminating BRONJ lesion bone with Raman spectroscopy - Xia, Chengwan; Pu, Yumei; Zhang, Qian; Hu, Qingang; Wang, Yuxin (Frontiers in Endocrinology, 2023)
Background With the frequent use of Bisphosphonates (BPs), the morbidity of BP-related osteonecrosis of the jaw (BRONJ) is also increasing. However, the prevention and treatment of BRONJ is faced with enormous challenges. This study aimed to illuminate the influence of BP administration in the rat mandible and explore the feasibility of discriminating BRONJ lesion bone with Raman spectroscopy. Materials and methods First, we explored the time- and mode-dependent effects of BP administration on the rat mandible with Raman spectroscopy. Second, the BRONJ rat model was constructed, and the lesion and healthy bone components were analyzed using Raman spectroscopy. Results When only BPs were administered, no rats showed BRONJ symptoms, and no difference could be found in the Raman spectra. However, when combined with local surgery, six (6/8) rats showed BRONJ symptoms. The Raman spectra also showed a significant difference between the lesion and healthy bone. Conclusion In the progression of BRONJ, BPs and local stimulation play an essential role. Both BPs administration and local stimulation need to be controlled to prevent BRONJ. Moreover, BRONJ lesion bone in rats could be discriminated with Raman spectroscopy. This novel method would become a complement in the treatment of BRONJ in the future.